1996
DOI: 10.1093/bja/76.5.685
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic responses to incision and sternotomy in relation to the auditory evoked potential and spontaneous EEG

Abstract: We investigated the effect of incision and sternotomy on the auditory evoked potential (AEP) and EEG, to try to predict a haemodynamic response to incision or sternotomy using the AEP and EEG in 41 patients undergoing cardiac surgery during propofol and alfentanil anaesthesia. The AEP and EEG were recorded before incision, between incision and sternotomy, and after sternotomy. Peak latencies and amplitudes of AEP peaks V, Na, Pa, Nb, Pb and Nc were determined. From the EEG the median, spectral edge and peak po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
0
14
0
3
Order By: Relevance
“…Recent studies investigating the EEG effects of noxious stimulation have identified that changes in mid‐range EEG frequencies – as typified by the F 50 – are specific for noxious stimulation in human beings, sheep and horses (De Beer et al. 1996; Morris et al.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigating the EEG effects of noxious stimulation have identified that changes in mid‐range EEG frequencies – as typified by the F 50 – are specific for noxious stimulation in human beings, sheep and horses (De Beer et al. 1996; Morris et al.…”
Section: Discussionmentioning
confidence: 99%
“…Some have identified de‐synchronization associated with nociceptive stimulation (Rampil & Matteo, 1987; Wilder‐Smith et al. , 1995; de Beer et al. , 1996; Schwender et al.…”
Section: The Eeg As a Tool To Assess Pain In Animalsmentioning
confidence: 99%
“…A large number of studies have been carried out to investigate the effect of a clinical nociceptive stimulus on the EEG of anaesthetized patients and have produced varying findings. Some have identified de-synchronization associated with nociceptive stimulation (Rampil & Matteo, 1987;Wilder-Smith et al, 1995;de Beer et al, 1996;Schwender et al, 1996).…”
Section: Studies Investigating Eeg Changes During Noxious Stimulationmentioning
confidence: 99%
“…The electroencephalogram (EEG) has been extensively investigated as a tool to monitor anaesthetic depth in human beings and has also been studied in horses (Rampil & Matteo 1987; White & Boyle 1989; Drummond et al. 1991; De Beer et al. 1996; Otto et al.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the EEG during noxious surgical stimulation have been identified in human beings (Rampil & Matteo 1987; Wilder‐Smith et al. 1995; De Beer et al. 1996; Schwender et al.…”
Section: Introductionmentioning
confidence: 99%